Membrane engineering in the circular economy : renewable sources valorization in energy and downstream processing in agro-food industry - Iulianelli, Adolfo; Cassano, Alfredo; Conidi, Carmela; Petrotos, Konstantinos (Elsevier, 2022)
Membrane Engineering in the Circular Economy: Renewable Sources Valorization in Energy and Downstream Processing in Agro-food Industry describes the modification of the general concept of "waste," including waste valorization as added-value products that are useful for energy production and biotechnology industries. Speaking to the relevance of this new vision, the book highlights the fundamentals of membrane operations in the exploitation of renewable sources for energy production and the valorization of agro-food waste at the industrial level. This book is an excellent resource for researchers, biologists, membranologists and engineers in chemistry, biochemical engineering, food sciences and the agro-food refinery industry.